Metode, Tantangan, dan Strategi Pembelajaran Keterampilan Membaca Bahasa Arab: : Tinjauan Literatur Sistematis - Anang Fajar Hasbi (Balai Bahasa Provinsi Riau, 2025)
Reading proficiency in Arabic is a fundamental and crucial skill for accessing religious texts such as the Qur'an, Hadith, and academic texts in the field of Islamic studies. This study examines strategies for teaching Arabic reading skills through a Systematic Literature Review (SLR) focusing on instructional techniques, challenges faced by non-native Arabic learners, and strategies for reading religious and academic texts. The researcher had taken 14 selected articles out of 750 identified articles by means of Publish or Perish, Semantic Scholar, Google Scholar, and other additional tools such as Mendeley and PRISMA for descriptive analysis purpose. Based on the SLR of the 14 journal articles, it was found that problem-based methods are effective in developing students’ analytical skills, while context-based approaches support deeper understanding of verses or texts. The study also highlights the importance of utilizing modern technologies such as interactive learning applications to boost student motivation and engagement. In addition, student collaboration through group discussions has been identified as a strategy that strengthens comprehension of both academic and religious texts. However, the study also identifies shortcomings in traditional approaches that overly emphasize grammar without practical context, as well as challenges in designing adaptive learning materials. This study offers practical guidance for educators in designing teaching strategies that align with learners’ needs in the digital era, thereby addressing the challenges of Arabic language learning more effectively.